Value engineering development in Malaysia: a diffusion study / Aliza Ramli - Ramli, Aliza (2010)
The increased global competition and complexity within the Malaysian automotive and construction industries have led organizations to find ways to maximize their products' values, processes, projects or services within a total system while controlling the costs. This can be achieved through Value Engineering (yE), one of the key methods in cost management, which aims to provide better products or services for less cost. Research has been lacking in examining corporate adoption of value appraisal tools such as VE in terms of product development. Little attempt also has been made in the literature to examine and explain the diffusion of VE at individual, organizational and industry levels within Malaysian industries. In addition, the cumulative knowledge on why and how organizations adopt and implement innovations from the theoretical and practical perspectives is still lacking. Increasing competitive pressures and gaps revealed from the literature reviewed provide an opportunity for such study within the Malaysian industries to be carried out. Hence, the main objective of this study is to explore and explain the development of VE and its practice within identified Malaysian automotive components manufacturing and construction organizations, and both the industries using Rogers' (2003) theory of diffusion of innovation. Dual methods, combining both qualitative and quantitative approaches were adopted, to provide a complementary perspective. The QUAL method (Case Study 1 and Case Study 2) was conducted prior to the QUAN (Survey 1 and Survey 2), suggesting sequential triangulation used in the design. However, the case study method was central to the research process. The case study findings were able to show strong relationships between several environmental factors (external and internal) and VE adoption by case companies.